ECCO Essential Requirements for Quality Cancer Care: Colorectal Cancer. A critical review. (February 2017) - Beets, Geerard; Sebag-Montefiore, David; Andritsch, Elisabeth; Arnold, Dirk; Beishon, Marc; Crul, Mirjam; Dekker, Jan Willem; Delgado-Bolton, Roberto; Fléjou, Jean-François; Grisold, Wolfgang; Henning, Geoffrey; Laghi, Andrea; et al.
Abstract: Background: ECCO essential requirements for quality cancer care (ERQCC) are checklists and explanations of organisation and actions that are necessary to give high-quality care to patients who have a specific tumour type. They are written by European experts representing all disciplines involved in cancer care. ERQCC papers give oncology teams, patients, policymakers and managers an overview of the elements needed in any healthcare system to provide high quality of care throughout the patient journey. References are made to clinical guidelines and other resources where appropriate, and the focus is on care in Europe. Colorectal cancer: essential requirements for quality care Colorectal cancer (CRC) is the second most common cause of cancer death in Europe and has wide variation in outcomes among countries. Increasing numbers of older people are contracting the disease, and treatments for advanced stages are becoming more complex. A growing number of survivors also require specialist support. High-quality care can only be a carried out in specialised CRC units or centres which have both a core multidisciplinary team and an extended team of allied professionals, and which are subject to quality and audit procedures. Such units or centres are far from universal in all European countries. It is essential that, to meet European aspirations for comprehensive cancer control, healthcare organisations implement the essential requirements in this paper, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis, to treatment, to survivorship. Conclusion: Taken together, the information presented in this paper provides a comprehensive description of the essential requirements for establishing a high-quality CRC service. The ECCO expert group is aware that it is not possible to propose a 'one size fits all' system for all countries, but urges that access to multidisciplinary units or centres must be guaranteed for all those with CRC.